Financial Inclusion in Romania : Issues and Opportunities - World Bank (World Bank, Washington, DC, 2020)
The report aims to explore and analyze the major gaps in financial inclusion and access to finance in Romania, as identified in the Technical Note on Financial Intermediation prepared in the context of the Financial Sector Assessment Program (FSAP) (2018). The FSAP technical note analyzed the factors at play explaining the relatively low and declining level of financial intermediation in Romania for both the household and the corporate segment and offered policy recommendations to support sustainable enhancement of financial intermediation. The report is organized as follows: chapter one conducts a geo-spatial mapping of financial inclusion and access to finance for both individuals and enterprises. Chapter two is a diagnostic assessment of the state of finance for agriculture and identifies constraints and potential opportunities. Chapter three provides an overview of the role of the cooperative financial institutions in financial inclusion especially in rural areas and recommendations how this may be enhanced.